ANALISIS POTENSI PEMANFAATAN SUNGAI TALLO MAKASSAR SEBAGAI ALUR PELAYARAN - Agusdiansyah, Dwi; Paotonan, Chairul; Rahman, Sabaruddin (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
One of the rivers with potential for development into a river transportation system in the city of Makassar is the Tallo River, which is approximately 22.2 km long. This river can connect the Tamalanrea sub-district with the coastal area of Makassar. Currently, the Tallo River is utilized as a transportation route to Lakkang Island, which is one of the tourist destinations. Based on the relatively wide characteristics of the river, the Tallo River can accommodate vessels with a relatively large draft. However, a study is needed to determine the maximum draft of vessels that can operate in the river based on water depth and air clearance at the Reformasi Toll Bridge. The objective of this research is to determine the maximum draft and freeboard of vessels that can operate in the Tallo River, identify areas of shoaling, and calculate the volume of dredging required. The research begins with literature review, collection of secondary and primary data, data analysis, and identification of shoaling points for calculating dredging volume. The data collected includes bathymetric data, tidal data, current data, bottom sediment data, and river discharge data. Based on the data analysis results, the maximum vessel draft before dredging is 1.0 m LWL with an air clearance of 1.9 m from the high tide water level. After dredging, the draft of vessels that can use the Tallo River is 1.5 m LWL. The locations requiring dredging are 13 points, with a total dredging volume of 1283.49.